1994
DOI: 10.1029/93jc02714
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐current interaction near the Gulf Stream during the Surface Wave Dynamics Experiment

Abstract: This paper presents a case study on the wave-current interaction near the local curvature of a Gulf Stream meander. The wave data were obtained from in situ measurements by a pitch-roll discus buoy during the Surface Wave Dynamics Experiment (SWA-DE) conducted off Wallops Island, Virginia, from October 1990 to March 1991. Owing to the advection of the Gulf Stream by the semidiurnal tide, the discus buoy was alternately located outside and inside the Gulf Stream. The directional wave measurements from the buoy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…In general, changes in wave characteristics are attributed to physical processes of wave refraction and/or straining (Holthuijsen and Tolman 1991) caused by the horizontal shear current. Recent studies using spaceborne altimeter data have indicated that strong ocean currents, such as the Kuroshio of the Pacific Ocean, exert a significant influence on wave characteristics (Hwang 2005); similar observations have been reported for a wide range of temporal and spatial scales (Tolman 1991;Wang et al 1994;Masson 1996). Moreover, wave-current interactions may generate so-called freak waves of extreme size (e.g., White and Fornberg 1998), as abnormal waves have been observed repeatedly in areas with strong currents (e.g., Lavrenov 1998).…”
Section: Introductionsupporting
confidence: 68%
“…In general, changes in wave characteristics are attributed to physical processes of wave refraction and/or straining (Holthuijsen and Tolman 1991) caused by the horizontal shear current. Recent studies using spaceborne altimeter data have indicated that strong ocean currents, such as the Kuroshio of the Pacific Ocean, exert a significant influence on wave characteristics (Hwang 2005); similar observations have been reported for a wide range of temporal and spatial scales (Tolman 1991;Wang et al 1994;Masson 1996). Moreover, wave-current interactions may generate so-called freak waves of extreme size (e.g., White and Fornberg 1998), as abnormal waves have been observed repeatedly in areas with strong currents (e.g., Lavrenov 1998).…”
Section: Introductionsupporting
confidence: 68%
“…By using a wave refraction model, Wang et al . [] showed that the focusing of wave rays by the Gulf Stream meander causes changes in wave direction/energy and directional spreading observed by in situ measurements. Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Holthuijsen and Tolman [1991] found that the current-induced wave refraction due to the strong current shear of the Gulf Stream could induce a considerable variation on wave heights. By using a wave refraction model, Wang et al [1994] showed that the focusing of wave rays by the Gulf Stream meander causes changes in wave direction/energy and directional spreading observed by in situ measurements. Liu et al [1994] also showed that mesoscale eddies can be detected from the synthetic aperture radar images via the influence of eddy currents on the surface wave fields.…”
Section: Introductionmentioning
confidence: 99%
“…Significant insights have been obtained by theoretical analysis of waves on currents with velocity depending on only one coordinate [ Longuet‐Higgins and Stewart , 1960, 1961; McKee , 1974; Basovich and Talanov , 1977; Hughes , 1978; Basovich et al , 1987; Thompson et al , 1988; Gotwols et al , 1988; Trulsen et al , 1990; Maltseva et al , 1995; van der Kooij et al , 1995]. Direct numerical integration of equations governing wave train trajectories and wave action balance has been used when simulating surface wave interaction with currents variable in two dimensions [ Irvine and Tilley , 1988; Liu et al , 1989; Brissette et al , 1993; Wang et al , 1994].…”
Section: Introductionmentioning
confidence: 99%